Women and business: Empirical study on economic constraints, legal conditions, and social support influencing women entrepreneurs in Malaysia and Poland - Beata Ślusarczyk; Sedigheh Moghavvemi; Shehnaz Tehseen (Entrepreneurial Business and Economics Review (EBER), 2023)
Objective: The study aimed to develop and validate three factors, i.e. economic constraints, legal conditions, and social support that influence women entrepreneurs' managerial skills. Research Design & Methods: A conceptual model was developed based on the literature review, and the data collected from 120 women entrepreneurs in Poland was utilised to construct the scale. The items were generated after validity, reliability, and exploratory factor analysis were conducted with SPSS software. The final developed scale was validated among 140 women entrepreneurs in Malaysia and the data was analysed through structural equation modelling (Amos). Findings: The results show that economic constraints, legal conditions, and social support are the main factors that influence the managerial skills of women entrepreneurs. Further analysis shows that economic constraints, legal conditions, and social support, vary across countries and influence women entrepreneurs' businesses. Women entrepreneurs in Poland consider assertiveness, risk-taking, responsibility, patience, and diligence as essential features of entrepreneurs, while women entrepreneurs in Malaysia believe patience, independence, self-confidence, responsibility, courage, and the ability to work with people are the most important features. Implications & Recommendations: This study identified the main factors that impact women entrepreneurs and highlights that the factors could have a significant effect on their managerial skills, which can provide knowledge for industry players and government officials who want to ease the start-up process and prevent failures. Contribution & Value Added: This study advances knowledge about the various factors influencing women's businesses in emerging countries like Malaysia and developed countries like Poland. It also makes a practical contribution by helping to develop policies that can encourage entrepreneurship among women.
Keywords: L26; 330; women; entrepreneurship; socio-economic factors; legal conditions; Poland; Malaysia